2015
DOI: 10.1007/s11302-015-9446-7
|View full text |Cite
|
Sign up to set email alerts
|

Creatine, similarly to ketamine, affords antidepressant-like effects in the tail suspension test via adenosine A1 and A2A receptor activation

Abstract: The benefits of creatine supplementation have been reported in a broad range of central nervous systems diseases, including depression. A previous study from our group demonstrated that creatine produces an antidepressant-like effect in the tail suspension test (TST), a predictive model of antidepressant activity. Since depression is associated with a dysfunction of the adenosinergic system, we investigated the involvement of adenosine A 1 and A 2A receptors in the antidepressant-like effect of creatine in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…It has been indicated that stimulation of both hippocampal and striatal adenosine A1 receptors reduces monoaminergic transmission, whereas blockade of adenosine A1 receptor increases monoaminergic transmission . It was demonstrated that creatine and ketamine produced rapid antidepressant‐like effects by activating both adenosine A1 and A2A receptors . However, caffeine abolished the anti‐immobility effect in the tail suspension test, indicating the importance of the adenosinergic system in the antidepressant‐like effect of creatine and ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that stimulation of both hippocampal and striatal adenosine A1 receptors reduces monoaminergic transmission, whereas blockade of adenosine A1 receptor increases monoaminergic transmission . It was demonstrated that creatine and ketamine produced rapid antidepressant‐like effects by activating both adenosine A1 and A2A receptors . However, caffeine abolished the anti‐immobility effect in the tail suspension test, indicating the importance of the adenosinergic system in the antidepressant‐like effect of creatine and ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were suspended 50 cm above the floor by adhesive tape placed approximately 1 cm from the tip of the tail. The immobility time was manually recorded during a 6-min session, and mice were considered immobile only when they hung passively and completely motionless [49][50][51].…”
Section: Tstmentioning
confidence: 99%
“…It was also shown that increasing A 1 receptor expression evokes resilience against a depressive-like behavior in the FST and TST as well as exerts an antidepressant-like effect in a chronic stress model (Serchov et al 2015). These data suggest that antidepressant-like effect is related to activation of A 1 receptors, but this observation may not be relevant to classic antidepressants in view of the fact that DPCPX and ZM241385 did not prevent the anti-immobility effect of fluoxetine in the FST (Cunha et al 2015). Of note, in a chronic stress model of depression, contradictory results on the effectiveness of classic antidepressants and an agent transformed in vivo to endogenous glutamate N -methyl- d -aspartate (NMDA) receptor antagonist, kynurenic acid, were shown (Biagini et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the antidepressant-like effect of creatine and ketamine, fast-acting antidepressant agents targeting the glutamatergic system, but not fluoxetine, was abolished by caffeine, DPCPX (a selective adenosine A 1 receptor antagonist), and ZM241385 (a selective adenosine A 2A receptor antagonist), while the administration of ineffective doses of creatine or ketamine combined with CHA (a selective adenosine A 1 receptor agonist), DPMA (a selective adenosine A 2A receptor agonist), or dipyridamole (an adenosine transporter inhibitor) produced a synergistic antidepressant-like effect in the TST (Cunha et al 2015). It was also shown that increasing A 1 receptor expression evokes resilience against a depressive-like behavior in the FST and TST as well as exerts an antidepressant-like effect in a chronic stress model (Serchov et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation